2014
DOI: 10.1007/s10498-014-9228-9
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Nature of Phosphorus in Subtropical Lake Sediments

Abstract: The phosphorus (P) composition of sediment profiles in three subtropical lakes of contrasting trophic state in Florida, USA, was determined by sequential fractionation and solution 31 P NMR spectroscopy. Sediment from Lake Annie, an oligo-mesotrophic sinkhole with moderately acidic sediment (pH 5.4; loss on ignition 58 %), contained higher total P concentrations than sediment from eutrophic Lake Okeechobee (pH 7.7, loss on ignition 36 %) and hyper-eutrophic Lake Apopka (pH 7.5, loss on ignition 69 %). The chem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 69 publications
(88 reference statements)
0
10
0
Order By: Relevance
“…Because of concerns over post-depositional P mobility, some investigators have questioned the utility of sediment P fractions as proxies for eutrophication [ 37 ], [ 38 ]. We argue, however, that the complex and very different stratigraphies of H 2 O-P, HE-P and TP, as well as discrete peaks in concentration of these variables in LH-6-13 demonstrate a lack of post-depositional mobility for these P forms in the Lake Harris core.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of concerns over post-depositional P mobility, some investigators have questioned the utility of sediment P fractions as proxies for eutrophication [ 37 ], [ 38 ]. We argue, however, that the complex and very different stratigraphies of H 2 O-P, HE-P and TP, as well as discrete peaks in concentration of these variables in LH-6-13 demonstrate a lack of post-depositional mobility for these P forms in the Lake Harris core.…”
Section: Discussionmentioning
confidence: 99%
“…2,500 cal a BP. Kenney et al [ 28 ] referred to the HE-P fraction as equivalent to polyphosphate (Poly-P), but HE-P may also include other organic components of sediment P [ 38 ], [ 39 ]. To avoid confusion, we use the operationally defined term HE-P here.…”
Section: Discussionmentioning
confidence: 99%
“…Significant P loading from sediments has been observed in environments as diverse as estuarine (Roy et al, 2012), boreal (Tammeorg et al, 2015), and subtropical (Xie et al, 2003;Grunwald et al, 2006;Torres et al, 2014), and in bodies of water as large as the North American Great Lakes (Kane et al, 2014) and Lake Taihu in China (You et al, 2007). Excess P inputs are often stored in lentic systems as "legacy" P (Sharpley et al, 2013), which is P that has been accumulating in sediments over time and may take tens to thousands of years to flux out of the system (Kleinman et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that sediment acted as a sink or a source of P to the overlying water in Poyang Lake. The P concentration gradient between sediment and overlying water, porosity, particle size, as well as some other factors were considered to have influenced the DRP fluxes (Torres et al 2014). Since this model did not consider the influence of bio-perturbation, the horizontal migration of phosphorous in the water body, and the wave disturbance of sediments, the results of Fick's Law were, in general, slightly lower than the real diffusion flux.…”
Section: ¡1mentioning
confidence: 99%